Impact of Pay Revision on Expenditure of Urban Local Bodies in Thanjavur Region - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
In India, an increasing trend towards urbanisation has been recorded from the very beginning of this present century. Pay revision influences the financial expenses of various sectors. Urban local bodies (ULB) have struggled to meet out the expenses and hence the pay revision makes more burdens to them. There is a need to study to how pay revision impacts financials of ULBs. The present study is a secondary data research collected from the ULBs of Thanjavur region from 2004-2014. The study used comparative analysis by ANOVA technique.